(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Pain in the face and oral cavity due to pathology of the structures of the trigeminal nerve requires a thorough topical diagnosis to determine the level of damage. The collection of anamnesis, especially the description of the pain phenomenon by the patient, as well as an objective study of clinical manifestations, make it possible to determine first the level of damage, and then the cause of the disease. Anatomy of the trigeminal nerve.